Facile Synthesis of π-Conjugated Heteroaromatic Compounds via Weak-Base-Promoted Transition-Metal-Free C–N Coupling - Senoo, Takahiro; Inoue, Aiko; Mori, Keiji (Synthesis, 2020)
A K2CO3-promoted transition-metal-free C–N coupling reaction was developed. When a solution of 1-(2-aminophenyl)-8-iodonaphthalenes in DMSO was treated with 2.5 equivalents of K2CO3 and 5.0 equivalents of MeI, intramolecular C–N coupling reaction proceeded smoothly even at low temperature (room temperature) to afford various heteroaromatic compounds in good chemical yields. Additional experiments suggested that this reaction might have proceeded through an unusual SNAr reaction between haloarenes and a bulky tertiary amine moiety.
Keywords: heterocycles; coupling; metal-free; π-conjugated molecule; base-promoted reaction